Partisipasi Masyarakat dalam Implementasi Kebijakan Pencegahan Covid-19 di Kalurahan Nogotirto, Kapanewon Gamping - Nuril Mawaddah; Muhammad Khozin (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
At the beginning of 2020, Covid-19 was officially declared as a global pandemic outbreak that had an impact on all sectors of life by the World Health Organization (WHO). In preventing this virus, community participation is important. In this case, the community at Nogotirto Village also participates actively in the efforts to prevent Covid-19 by obeying the policies and recommendations set by the government. This study aims to determine the community participation in the implementation of Covid19 prevention policies and provide input to Nogotirto Village Government. This research method employed a qualitative approach through observational data collection techniques, interviews and documentation. The technical analysis of the data used was data reduction, data presentation and drawing conclusions. Based on the results of this study, the community participation at Nogotirto Village in general is good even though the community participation has not been maximized. The form of participation of Nogotirto community in the Covid-19 prevention process is clearly tangible and not tangible. In addition, the factors supporting community participation in preventing Covid-19 at Nogotirto are the willingness, ability and opportunity factors. However, the inhibiting factors for community participation in preventing Covid-19 at Nogotirto are the lack of education, fanaticism towards religion and also lack of trust in the government. In the Covid-19 prevention process, the government is expected to be more consistent in carrying out prevention activities and supervising community activities, especially in public places